Prevalence and Infestation of Ectoparasite in Dabung Ducks in Some Districts in Bangkalan Madura - Prawasa, Ramadhiniyanti Putri Alif; Nunuk Dyah Retno Lastuti; Dadik Raharjo; Poedji Hastutiek; Endang Suprihati; Dian Ayu Permatasari (Journal of Parasite Science, 2023)
Identify the type of ectoparasite prevalence and infestation pattern of ectoparasite on Dabung duck in Bangkalan Madura regency. This research conducted from February to April 2022 with sample of 55 tails and identified in parasitology laboratory of the Veterinary Parasitology Division, Faculty of Veterinary Medicine, Airlangga University, Surabaya with the permanent mounting method without coloring. This research was a descriptive research, study survey, and cross sectional study analytical. The type of ectoparasite that attacked Dabung duck in Geger subdistrict, Dabung village and Galis subdistrict, Pekaan Dajah village were Menacanthus stramineus, Menopon gallinae, Lipeurus caponis with a prevalence of 100% from a sample 55 tails of Dabung duck. The analysis results of infestation pattern of ectoparasite infestation on Dabung ducks used correspondence text on the body regions of Dabung ducks in Geger subdistrict, Dabung village showed that M. stramineus ticks on chest region, M. gallinae in head neck region and L. caponis in wing region. Burneh subdistrict, Burneh village founded M. stramineus ticks in abdomen region, M. gallinae in head-neck region, and L. caponis in wing region. Galis subdistrict, Pakaan Dajah village showed that M stramineus lice in head-neck region, L. caponis in wing region and M. gallinae in spine region.